2021
DOI: 10.1177/1350650120987930
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of waste vegetable oil methyl esters as lubricant oil

Abstract: Increasing environmental awareness and threats to the environment have made the recycling of biomass products necessary. The goal of this paper is to study the tribological properties of fatty acid methyl esters derived from waste frying oils under different lubrication conditions. For this purpose, the performance of candidate fatty acid methyl esters was compared with a mineral base oil. For the determination of tribological properties, a pin-on-disc wear tester was used. The experiments were carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Organic additives can also provide effective lubrication, such as fatty acid methyl esters [96], boron-nitrogen modified soybean oil [97], moringa oil [98], organic friction modifiers (OFMs) [99], isooctyl furan dicarboxylate (isooctyl-FD) [100], N-octadecyl-D-gluconamides (NOG) [101], diblock polymeric friction modifier (PFM) [102], transesterified olax scandens oil [103], polyisobutylene (PIB) [104], thermo-oxidized Jatropha bio-oil [105], methyl oleate derived multifunctional additive [106], oleic acid Fig. 6 Properties of glass-fiber reinforced PA66 using as friction pair [54].…”
Section: Lubricant Additivesmentioning
confidence: 99%
“…Organic additives can also provide effective lubrication, such as fatty acid methyl esters [96], boron-nitrogen modified soybean oil [97], moringa oil [98], organic friction modifiers (OFMs) [99], isooctyl furan dicarboxylate (isooctyl-FD) [100], N-octadecyl-D-gluconamides (NOG) [101], diblock polymeric friction modifier (PFM) [102], transesterified olax scandens oil [103], polyisobutylene (PIB) [104], thermo-oxidized Jatropha bio-oil [105], methyl oleate derived multifunctional additive [106], oleic acid Fig. 6 Properties of glass-fiber reinforced PA66 using as friction pair [54].…”
Section: Lubricant Additivesmentioning
confidence: 99%
“…Various studies have reported enhanced machining performance with vegetablebased MWFs compared with petroleum-based MWFs in reduced machining forces, better workpiece surface finish, low tool wear and improved tool life. [7][8][9][10][11] Gajrani et al 12 compared commercial vegetable-based bio-cutting fluid (BCF) with petroleum-based mineral oil. Results show that the BCF was highly biodegradable and was able to reduce the machining forces and improved the surface finish of the machined workpiece.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have recently explored the possibility of using vegetable oil as a lubricant. e results are promising; vegetable oil has a good chance of being a better alternative to mineral oil both economically and environmentally [1][2][3][4]. In the contemporary world, biodiesel has continually received great attention as being an alternative biodegradable and nontoxic renewable source of fuel.…”
Section: Introductionmentioning
confidence: 99%